Pengaruh Citra Merek, Kualitas Produk Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Pada E-Commerce Bukalapak Di Kota Batam - Nurhaida; Realize (Komunitas Dosen Indonesia, 2023)
Bukalapak, which was started on January 10, 2010 by Achmad Zaky, Nugroho Herucahyono, and Muhamad Fajrin Rasjid, is one of the largest e-commerce companies in Indonesia created by the nation's children. Bukalapak is an online marketplace where transactions can be made. Several e-commerce businesses that compete with Bukalapak, such as Shopee, Lazada, and Tokopedia, continue to dominate the Indonesian market competition. The problem with Bukalapak has not been able to compete with other e-commerce brand images, then the quality of the products provided cannot match consumer demand, and there are still many negative reviews given by consumers so that they can influence purchasing decisions. With observable objectives such as brand image, product quality and consumer trust can influence purchasing decisions at e-commerce Bukalapak in Batam City. This study uses a descriptive research strategy based on a quantitative approach. The purpose of this kind of descriptive research is to strengthen the researcher's analysis and final conclusions by providing a clear and concise description of the conditions to be studied, with the help of a literature study. Data analysis techniques that can be used include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination analysis (R2), t test and f test. The results of the study can conclude that brand image, product quality and consumer trust partially and simultaneously can have a positive and significant impact on purchasing decisions at e-commerce Bukalapak in Batam City